2020
DOI: 10.1080/25751654.2020.1766164
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Fuel Cycle and the Proliferation “Danger Zone”

Abstract: Horizontal nuclear proliferation presents what is sometimes referred to as the "Nth country problem," or identifying which state could be next to acquire nuclear weapons. Nuclear fuel cycle technologies can contribute to both nuclear power generation and weapons development. Consequently, observers often view civilian nuclear programs with suspicion even as research on nuclear latency and the technological inputs of proliferation has added nuance to these discussions. To contribute to this debate, I put forth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…More recently, a 2017 survey indicated that approximately 69% of Japanese would want Japan to remain non-nuclear even if Pyongyang did not denuclearize (Genron NPO and East Asia Institute 2017). The public's strong disapproval of domestic proliferation is especially notable considering Japan's advanced nuclear energy program and achievement of "nuclear latency" (Fuhrmann and Tkach 2015;Mehta and Whitlark 2017;Herzog 2020). A 2018 nationally representative crisis simulation experiment further revealed that a staggering 85% of the Japanese population would not support US use of nuclear weapons against North Korea, even if that country launched a nuclear strike on Japan (Allison, Herzog, and Ko 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a 2017 survey indicated that approximately 69% of Japanese would want Japan to remain non-nuclear even if Pyongyang did not denuclearize (Genron NPO and East Asia Institute 2017). The public's strong disapproval of domestic proliferation is especially notable considering Japan's advanced nuclear energy program and achievement of "nuclear latency" (Fuhrmann and Tkach 2015;Mehta and Whitlark 2017;Herzog 2020). A 2018 nationally representative crisis simulation experiment further revealed that a staggering 85% of the Japanese population would not support US use of nuclear weapons against North Korea, even if that country launched a nuclear strike on Japan (Allison, Herzog, and Ko 2019).…”
Section: Introductionmentioning
confidence: 99%